KOLABORASI PEMERINTAH KABUPATEN LUMAJANG DENGAN GERAKAN PRAMUKA DALAM PENYELENGGARAAN HUNIAN SEMENTARA BAGI PENYINTAS ERUPSI GUNUNG SEMERU 2021 - TAQIY, MUCHAMMAD DAFFA NAUFAL; Kurniawan, Badrudin (Universitas Negeri Surabaya, 2023)
Indonesia is traversed by volcanic eruption-prone routes in a series of passages of The Pacific Ring Of Fire which causes the areas it traverses to frequently experience earthquakes and volcanic eruptions. This is what causes Indonesia to be vulnerable and have the potential for volcanic disasters. One of the natural disasters that occurred in East Java was the eruption of Mount Semeru. Many efforts have been made by the Lumajang Regency Government to deal with the impact of the eruption, one of which is the provision of temporary housing for victims in collaboration with the East Java Scout Movement. The purpose of this research is to analyze the process of cooperation to the form of cooperation between the Government of Lumajang Regency and the Scout Movement of East Java in disaster management after the eruption of Mount Semeru. This study uses descriptive qualitative research methods with data collection techniques through observation, interviews, and documentation. This study uses the Collaboration Governance model according to Ansell and Gash (2007), with 4 variables namely starting conditions, facilitative leadership, institutional design, and collaborative processes. The results of the study showed that the collaboration between the Government of Lumajang Regency and the Scout Movement to organize temporary housing for survivors of the 2021 Mount Semeru eruption was well achieved to improve the welfare of the people affected by the eruption of Mount Semeru. In the collaboration process, there are 5 stages including face-to-face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes. Indonesia dilalui jalur gunung api rawan erupsi dalam rentetan jalur lintasan The Pasific Ring Of Fire yang menyebabkan daerah yang dilaluinya sering mengalami gempa bumi dan gunung erupsi. Inilah yang menyebabkan Indonesia rawan dan memiliki potensi bencana gunung berapi. Salah satu bencana alam yang terjadi di Jawa Timur yaitu erupsi Gunung Semeru. Banyak upaya yang telah dilakukan oleh Pemkab Lumajang untuk menanggulangi dampak erupsi, salah satunya penyelenggaraan hunian sementara bagi korban yang berkolaborasi dengan Gerakan Pramuka Jawa Timur. Tujuan dari penelitian ini adalah untuk menganalisis proses kerjasama hingga bentuk kerjasama Pemerintah Kabupaten Lumajang dengan Gerakan Pramuka Jawa Timur dalam penanggulangan bencana pasca erupsi Gunung Semeru. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Penelitian ini menggunakan model Collaboration Governance menurut Ansell dan Gash (2007), dengan 4 variabel yaitu starting condition, facilitative leadership, institutional design, dan collaborative process. Hasil penelitian diperoleh bahwa kolaborasi antara Pemerintah Kabupaten Lumajang dengan Gerakan Pramuka dalam upaya penyelenggaraan hunian sementara bagi penyintas erupsi Gunung Semeru tahun 2021 tercapai dengan baik dalam upaya meningkatkan kesejahteraan masyarakat yang terdampak erupsi Gunung Semeru. Pada proses kolaborasi terdapat 5 tahapan diantaranya faces to faces dialogue, trust building, commitment to process, shared understanding, dan intermediate outcome.